2017
DOI: 10.1590/1807-1929/agriambi.v21n4p285-289
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity of ‘sucupira-branca’ (Pterodon emarginatus Vogel) fruits

Abstract: A B S T R A C T'Sucupira-branca' (Pterodon emarginatus Vogel) is a tree from 'Cerrado' and stands out mainly for its pharmacological properties; however, there are no technological information about its post-harvest operations. Thus, the aim of this study was to determine the sorption isotherms of 'sucupira-branca' fruits for different air conditions and obtain the values of desorption isosteric heat, depending on the equilibrium moisture content of the product. The equilibrium moisture content of 'sucupira-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…It can be observed that the harmonic mean had values lower than the range of isokinetic temperature, showing that the process is controlled by enthalpy. These results are consistent with those found by several researchers who have successfully applied the isokinetic theory to the sorption of the most diverse products (Hassini et al, 2015;Goneli et al, 2016;Oliveira et al, 2017;Resende et al, 2017;Silva et al, 2018;Campos et al, 2019).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It can be observed that the harmonic mean had values lower than the range of isokinetic temperature, showing that the process is controlled by enthalpy. These results are consistent with those found by several researchers who have successfully applied the isokinetic theory to the sorption of the most diverse products (Hassini et al, 2015;Goneli et al, 2016;Oliveira et al, 2017;Resende et al, 2017;Silva et al, 2018;Campos et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…This occurs because the adsorption heat is a measure of the energy released in the sorption of water in the product (Rizvi, 1995), being considered an indication of the intermolecular forces of attraction between the sorption sites and the water vapor (Wang & Brennan, 1991), so the higher the moisture content of the product, the lower the adsorption heat due to the lower number of bonds between the sorption sites. Oliveira et al (2017), studying the isosteric heat of sucupira-branca (Pterodon emarginatus Vogel) fruits, observed similar behavior for the integral isosteric heat, which ranged from 3,477.54 to 15,375.89 kJ kg -1 within the moisture content range from 10.4 to 4.7% (d.b. ), respectively.…”
Section: Resultsmentioning
confidence: 79%
“…Desorption isotherms are unique for each product (Galdeano et al, 2018) and very important, since, once the breakeven point is known, it can estimate the time needed to reach it, avoiding unnecessary energy expenditure during the drying operations, and provide information about the safe moisture contents (Botelho et al, 2019). In turn, isosteric heat is considered an essential parameter in energy demanded on drying processes because it is related to the amount of energy to remove the free water (Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%